Scenari di neurocivilizzazione (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
Neuroscience develops a “neuro-civilization” by certain strategies: definition of the role of Neuroscientists, new social paradigms (e.g. the concept of normality), substitution of traditional legal sources with neuroscientific standards. It may be a risk if a certain idea of normality imposes itself for current practices, not for theoretical reasons.
Keywords: Neurolaw; Neuroethics; Normality; Involuntary treatments; Direct brain intervention